Influence of back tension on wire deformation heterogeneity and texture intensity: A coupled macro-micro calculation study - Rui Cai; Chunni Jia; Yong Zhao; Zhendan Yang; Tengyuan Liu; Xiangjun Chen; Pei Wang; Dianzhong Li (Journal of Materials Research and Technology)
Pearlitic steel wires are typically produced through cold drawing process, where the wire is pulled through drawing dies by external forces, leading to diameter reduction and length elongation. To control and stabilize this elongation, back tension is usually applied, altering the stress state and plastic deformation during the drawing process. However, the effects of back tension on the overall mechanical properties of the wire have not been systematically studied. The aim of this study is to investigate how back tension influences deformation heterogeneity and texture evolution in pearlite wire during cold drawing, using both simulation and experimental methods. A macroscopic drawing model, coupled with microscopic crystal plasticity representative volume element (RVE), is developed to capture and analyze the texture evolution. Calculation results indicate that higher back tension reduces deformation heterogeneity in the wire, which is consistent with experimental observations. However, excessive back tension can cause necking. These findings suggest that back tension plays a critical role in controlling the deformation behavior, affecting the final mechanical properties of the drawn wire. Specifically, back tension affects the bending property of the steel wire by influencing the axial residual stress during wire drawing and enhances the torsional property by strengthening the <110> fiber texture intensity. Additionally, it also influences the activation of slip systems by affecting the resolved shear stress. These insights can guide the optimization of the drawing process to achieve desired mechanical properties.